Lampyridae: History of the type species of the genus Luciola, updated checklist of North African fireflies, and other taxonomic and faunistic notes - Fanti, Fabrizio (Baltic Journal of Coleopterology, 2024)
This work provides an updated checklist of the Lampyridae of North Africa, including a brief summary on the Lampyridae species excluded from this area. The taxonomic acts proposed here, are: Lampyris algeica Cros, 1924 incorrect subsequent spelling; Lampyris gridelli Geisthardt & Satô, 2007 incorrect subsequent spelling; Lampyris letourneuxi J. E. Olivier, 1884 stat. rest.; [Lampyris] lusitanica letournexi [sic] Keller & Martin, 2024 incorrect subsequent spelling; Nyctophila confusa variata var. rufilabris Geisthardt, 1982 incorrect original spelling; Lampyris (Nyctophila) heydeni J. E. Olivier, 1884 comb. rest.; Lampyris (Nyctophila) reichii reichii Jacquelin du Val, 1859 comb. rest.; Lampronetes mauritanica Motschulsky, 1853 nomen nudum; Pelenia Constantin, 2014 incorrect subsequent spelling; Pelania maritanica J. E. Olivier, 1907 incorrect subsequent spelling; Pelania mauretanica Guzmán Álvarez & De Cock, 2010 incorrect subsequent spelling, De Cock & Guzmán Álvarez, 2014; Guzmán Álvarez & De Cock, 2017 incorrect subsequent spellings (name not available for the Code).